Geriatric Interdisciplinary Home Rehabilitation After Hip Fracture in People with Dementia – A Subgroup Analysis of a Randomized Controlled Trial - Karlsson Å (Dove Medical Press, 2020)
Åsa Karlsson,1 Monica Berggren,2 Birgitta Olofsson,3 Michael Stenvall,2 Yngve Gustafson,2 Peter Nordström,2 Nina Lindelöf1 1Department of Community Medicine and Rehabilitation, Geriatric Medicine and Physiotherapy, Umeå University, Umeå, Sweden; 2Department of Community Medicine and Rehabilitation, Geriatric Medicine, Umeå University, Umeå, Sweden; 3Department of Nursing and Department of Surgical and Perioperative Science, Orthopedics, Umeå University, Umeå, SwedenCorrespondence: Åsa KarlssonDepartment of Community Medicine and Rehabilitation, Geriatric Medicine, Umeå University, Umeå SE- 901 87, SwedenTel +46 90 785 87 66Email asa.karlsson@umu.sePurpose: To investigate if the effects of geriatric interdisciplinary home rehabilitation after hip fracture were different among people with dementia compared to those without dementia and to describe the overall outcome after hip fracture in people with dementia.Patients and Methods: A post hoc subgroup analysis of a randomized controlled trial was conducted including 205 people with hip fracture, aged ≥ 70, living in ordinary housing or residential care facilities. Early discharge followed by individually designed interdisciplinary home rehabilitation for a maximum of 10 weeks was compared to in-hospital geriatric care according to a multifactorial rehabilitation program. Outcomes were hospital length of stay (LOS), readmissions, falls, mortality, performance in activities of daily living (ADL), and walking ability.Results: Interdisciplinary home rehabilitation vs in-hospital care had comparable effects on falls and mortality between discharge and 12 months and on ADL and walking ability at 3 and 12 months regardless of whether the participants had dementia or not (P≥ 0.05 for all). Among participants with dementia, postoperative LOS was a median of 18 days (interquartile range [IQR] 14– 30) in the home rehabilitation group vs 23 days (IQR 15– 30) in the control group (P=0.254) with comparable numbers of readmissions after discharge. Dementia was associated with increased risk of falling (odds ratio [OR] 3.86; 95% confidence interval [CI]: 2.05– 7.27; P< 0.001) and increased mortality (OR 4.20; 95% CI 1.79– 9.92, P=0.001) between discharge and 12 months and with greater dependence in ADL and walking at 3 and 12 months compared to participants without dementia (P< 0.001 for all).Conclusion: The effects of geriatric interdisciplinary home rehabilitation vs in-hospital geriatric care did not differ in participants with and without dementia. However, the statistical power of this subgroup analysis was likely insufficient to detect differences between the groups. Dementia was associated with a substantial negative impact on the outcomes following the hip fracture. Our findings support offering interdisciplinary home rehabilitation after hip fracture to people with dementia.Keywords: accidental falls, activities of daily living, cognitive impairment, length of stay, walking ability